Effect of Urea-Molasses and Lactic Culture on Silage Fermentation of Cenchrus ciliaris - Pancholy, Rakesh; Mali, P C; Mathur, Dinesh (Annals of Arid Zone, 2016)
To study the effect of additives, urea, molasses and lactobacillus cultures, onÂ silage fermentation of Cmchrus ciliaris in arid regions, S treatments with different proportions Â of urea (1 and 2% OM) and molasses (8%) were studied in laboratory silos. MolassesÂ addition showed a significant effect (P<O.O1) on lactic acid production, pH and coliformÂ population, while crude protein levels of the silage increased to 9.29% and 12.27% (OM)Â on addition of 1% and 2% urea, respectively, Uniform addition of LAB culture at theÂ rate of 6% (cell concentration US x 106 cells gm’l) affected final silage quality only inÂ the presence of added molasses